PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP PENGUASAAN KONSEP SAINS DITINJAU DARI KEMAMPUAN AWAL SISWA - Susilawati -; Nyoman Sridana (Postgraduate, University of Mataram, 2015)
This study aims to find out: (1) the differences in science concept mastery of students who take guided inquiry learning model with conventional learning, (2) the differences in science concept mastery of students that prior knowledge high and low prior knowledge. This method of research is an quasi-experimental with factorial 2x2 analysis design. The subject of this study was ten class of 8th grade student in SMP 10 Mataram 2014/2015. Two class was chosen as sample using cluster random sampling technique, one classes as experimental group and one classes of control group. The research instrument is science mastery concept made by teacher. Data were analyzed using ANCOVA to find the effect of learning model and prior knowledge to science concept mastery. Analyses were performed using SPSS version 20 for Windows. Based on the analysis can be concluded that: 1) There are differences in science concept mastery of students who take guided inquiry learning model compared to conventional learning. 2) There is no difference in concept science mastery of students who have high and low prior knowledge of students.